'To arrive where we started, and know the place for the first time'. Issue 2 (1st January 2013) - Mumford, James
Abstract By permission of Oxford University Press (www.oup.com). Extract (3679w) from Ch. 3 'Context Neglected', (219w) from Ch. 4 'Grounds for Recognition' and (170w) 'Introduction' from Ethics at the Beginning of Life: A Phenomenological Critique by James Mumford (2013). Free permission: Author's own material. Intellectual stalemate in the abortion debate can be traced in part to its being framed as a standoff between religion and secular philosophy. While the former is thought to generate a broadly 'pro-life' position, the latter is associated with more 'pro-choice' thinking. This essay attempts to break free of this framing by criticising the philosophy informing 'pro-choice' positions, but not by resorting immediately to religious arguments but rather by drawing upon a rival philosophical tradition – the movement within twentieth and twenty-first Continental philosophy which was and is phenomenology. A phenomenological approach to human 'emergence', and in particular an application of the framework Heidegger developed in Being and Time (1927), leads to a radical questioning of whether contemporary English-speaking beginning-of-life ethics have adequately taken into account the way human beings come forth in the world.